1991
DOI: 10.1055/s-2007-999398
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia Versus Sedation During Broviac Catheter Placement

Abstract: Premature infants are capable of mounting physiologic and metabolic responses to pain. Systemic and local anesthesia reduce stress responses to major and minor surgical procedures. We evaluated the effects of local anesthesia (5 mg/kg lidocaine) preceded by either 1 mg/kg secobarbital (S) intravenously or by 2 micrograms/kg fentanyl (F) intravenously on the stress response to Broviac catheter placement. Twenty-nine premature infants ages 5 to 30 days, weighing between 650 and 1350 gm, were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…33,35,36 • Behavioral methods, including sucrose and nonnutritive sucking. 12,20,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] • Pharmacological agents for preemptive analgesia 20,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] (Table 4). …”
Section: Management Of Pain In the Newbornmentioning
confidence: 99%
See 2 more Smart Citations
“…33,35,36 • Behavioral methods, including sucrose and nonnutritive sucking. 12,20,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] • Pharmacological agents for preemptive analgesia 20,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] (Table 4). …”
Section: Management Of Pain In the Newbornmentioning
confidence: 99%
“…58,70 • Consider slow intravenous opioid infusion (morphine sulfate* or fentanyl citrate*). 73,76 • Consider using general anesthesia for the procedure. 15,70,76,91 Umbilical Catheter Insertion (Umbilical Arterial/Umbilical Venous)…”
Section: Central Venous Line Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…They preferred placement in the groin, through the long saphenous vein. An elegant prospective randomized study by Cordero et al [7] showed that low-dose fentanyl analgesia complemented local lidocaine anesthesia effectively. Our study capitalized on all these elements and confirmed that tunneled groin lines can be placed safely in neonates in the NICU under lidocaine local anesthesia with fentanyl analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a desired clinical effect, initial intravenous boluses of 0.5-2 mg/kg may be given every 2-5 min, followed by infusions of 0.2-2 mg/kg/h for maintained analgesia. [30][31][32] One blinded randomised controlled trial (RCT) found that a single dose of fentanyl given to ventilated preterm neonates (,32 weeks, n = 22) considerably reduced pain behaviours and changes in heart rate, and increased growth hormone levels. 30 Mean fentanyl infusion rates of 0.64 mg/kg/h in ventilated infants of ,34 weeks gestation and 0.75 mg/kg/h in infants of >34 weeks gestation produced adequate analgesia, stable blood pressures and few adverse effects in a case-control study.…”
Section: Fentanylmentioning
confidence: 99%